Assistance in strengthening oyster mushroom business management for people with disability of Restu Abadi - Hesti Respatiningsih; Dwi Irawati; Nurlaila Fatmawati; Tutik Rosiani; Aisya Putri Sintowati; Makhzumi Jundana; Dewi Siti Nur Aisyah; Nur Farichatul Ngaisah; Dewi Fitrianingsih (Universitas Muhammadiyah Magelang, 2022)
In order to address DPO Restu Abadi's business management issues, including limited oyster mushroom production capacity and quality, packaging, conventional product marketing with limited range, business legality, human resource management, and financial management, this community service is being performed. Culinary professionals, brand activists, and experts in oyster mushroom cultivation were all involved in this activity, which was carried out through training and mentoring practices. This program has been successful in raising the standard of packaging, including branding and labels, expanding the market reach with digital marketing, and processing business permissions (NIB and P-IRT). Whereas in the production aspect, the service team facilitates the addition of production facilities in the form of kumbung, baglog, and baglog sterilization equipment.